Expert opinions about the use of comprehensive nutrition protocol in practice for obesity prevention - Mojca Bizjak; Melita Peršolja; Lidija Zadnik Stirn (Nurses and Midwives Association of Slovenia, 2016)
Introduction: Obesity is associated with a number of chronic diseases. The research aimed to determine the effectiveness of nutrition assessment when using a comprehensive nutrition protocol at primary health service. Methods: A real life situation was analysed for the positive and negative factors in the newly formed comprehensive nutritional protocol. These factors were identified by a group decision-making and a SWOT Analysis (Strengths, Weaknesses, Opportunities and Treats) and subsequently numerically evaluated with the Analytic Hierarchy Process method which included expert opinions. Results: According to experts, the most important factors justifying the introduction of the protocol in practice are "equal treatment for all subjects" and "precisely prepared manual", followed by "individual treatment" and "health status improvements". The two most important negative factors are "dependence on other professionals" and "subjects will not be able to follow the protocol". Discussion and conclusion: Expert opinions favour the introduction of nutrition protocol in clinical practice to ensure equal treatment of all subjects, and enhance obesity prevention with the accompanying detailed instructions. For this reason, further research should address the foundation of dietetic counselling services at the primary level of healthcare, so that physicians could refer obese people to individual nutritional therapy, which may reduce the prevalence of obesity.